Insight into the influence of rare-earth promoter (CeO2, La2O3, Y2O3, and Sm2O3) addition toward methane dry reforming over Co/mesoporous alumina catalysts - Mahadi, Bahari; Herma Dina, Setiabudi; Nguyen, Trinh Duy; Phuong, Pham T. T.; Truong, Quang Duc; Aishah, Abdul Jalil; Nurul Aini, Razali; Vo, Dai-Viet N. (Elsevier, 2020)
Co/mesoporous alumina (MA) catalysts promoted with Ce, La, Sm, and Y were evaluated via methane dry reforming. Co particle dispersion on MA was evidently improved after promoter incorporation, resulting in smaller crystallite size and lesser Co agglomeration. Unlike Ce and La promoters, the employment of Y and Sm promoters reduced catalyst reducibility by strengthening Co-MA interaction. The reactant conversions improved in the order of YCo/MA > LaCo/MA > CeCo/MA > SmCo/MA > Co/MA, while the amount of carbon deposit was recorded with the sequence of Co/MA > SmCo/MA > LaCo/MA > CeCo/MA > YCo/MA. Additionally, YCo/MA attained the highest activity (CH4 conversion = 85.8%, CO2 conversion = 92.2%) and possessed the lowest carbon deposition (7.02%) due to great Co dispersion, small Co particle size with strong Co-MA interaction and higher oxygen storage capacity. H2/CO ratios were obtained within 0.78-0.86, slightly lower than 1 in consequence of the reverse water-gas shift.